Needs Analysis Of Physics Edupark Enrichment Book Batang Tabik Waterpark Design Integrated Problem-based Learning - Kinanti, Ihsania Ikrima; Rifai, Hamdi (PILLAR OF PHYSICS EDUCATION, 2023)
In general, visitors who come to the tourist attraction only have fun and capture their vacation moments, without realizing that there are many physics concepts in every game vehicle there. This research is a preliminary research that aims to analyze the needs of physics enrichment book development for Batang Tabik Waterpark edupark integrated with problem-based learning model. The type of research used is design research using the Plomp model. This research was conducted only up to the preliminary research stage consisting of student analysis, teacher analysis, and analysis of learning materials at Batang Tabik Waterpark. The data used in this study were taken from the results of student needs analysis and interviews with one physics teacher and 30 students of class X SMAN 3 Payakumbuh. Based on the results of the study, it is known that the physics edupark enrichment book integrated with problem-based learning models can motivate students in learning; show physics phenomena as a whole; help develop students' knowledge and skills; and help students master physics material. In addition, the Batang Tabik Waterpark tourist attraction can be used as a physics education park and as an object of enrichment book development in the form of a physics edupark enrichment book integrated with problem-based learning models equipped with photos and videos because of its many links to physics concepts. So it can be concluded that the physics edupark enrichment book Batang Tabik Waterpark is a suitable enrichment book if used as a physics edupark learning media.